EFFECT OF FORMULATION OF EMBLICA OFFICINALIS ON BIOCHEMICAL PARAMETERS IN WISTAR RATS - NARENDRA KUMAR SAVALA,; PARVATANENI NAGASRI HARITHA,; MANGAMOORI LAKSHMI NARASU, (The Bioscan, 2012)
Emblica officnalis formulation with ghee and honey is in wider practice in the Kerala, India as a rejuvenating agent. The objective of this paper is to study the effect of Emblica officinalis formulation on the following biochemical parameters like glucose, alkaline phosphotase, alkaline amino transferase, aspartate transferase, albumin, bilirubin, blood urea nitrogen, creatinine and total protein. The results indicate that there is a beneficial trend in some of the biochemical parameters within the normal ranges.